An exploratory study of recruitment and selection in professionalising local government : a case study of the City of Johannesburg Metropolitan Municipality - Jukuju, Nozuko (Stellenbosch : Stellenbosch University, 2025)
Thesis (MCom)--Stellenbosch University, 2025.